Trust in E-Commerce and Its Impact on the Purchase Intention of Consumers in MSME Stores in Chiapas - Mexico - García-Salirrosas, Elizabeth Emperatriz (2022)
The intention to buy online is an essential factor for the success of organizations of any size and sector. Getting consumers to have a high level of purchase intention predicts actual purchasing behavior of the products or services offered. This factor is associated with various variables of consumer purchasing behavior. Trust is presented as a variable that can drive this purchase intention. Therefore, the present study aimed to determine the impact of trust in e-commerce on the purchase intention of consumers in MSME stores in Chiapas-Mexico. The PERVAINCONSA questionnaire was applied to evaluate the variables trust and purchase intention, to 330 consumers who made purchases in online stores of an MSME in Chiapas. Through a linear regression analysis, it was found that trust is a predictor variable of the purchase intention in the electronic commerce of the MSMEs (R= .750; R2 =56%), finding a positive, direct and significant. It is concluded that the greater confidence in e- commerce by consumers, the greater their intention to purchase online.